STUDY OF THE KNOWLEDGE AND USE OF RESILIENT DENTURE LINING MATERIALS IN CLINICAL PRACTICE - Mariana Yankova; Todor Peev; Bozhidar Yordanov; Mariana Dimova-Gabrovska; Desislava Dimitrova (Peytchinski Publishing, 2021)
Introduction: Since the beginning of the last century until today, resilient resins have been used for the lining of partial and complete dentures with the aim to achieve more uniform distribution of masticatory pressure and to reduce the trauma of mucous membranes. The aim of this study was to investigate the knowledge and use of resilient denture lining materials (RDLMs) in clinical practice. Material and methods: The study was conducted among dental practitioners and dental technicians in 2016. A direct survey method was used, with a questionnaire containing 11 questions. Results: Over half (53.4%, n = 133) of the respondents do not use RDLMs in their practice. In the cases of retentive prosthetic field or prosthetic field with advanced atrophy, the respondents focus mainly on the surgical preparation of the prosthetic field and recommend the use of RDLMsif there are exostosis-related pain symptoms (≈41%, n = 103) or painful neurogenic points (≈ 44%, n = 105). One-third of the respondents prefer the use of long-term RDLMs, and 73% prefer to apply the indirect lining technique. Conclusion: The various types of RDLMs and their characteristics are well-known by the dental practitioners and dental technicians but rarely used, due to a number of unresolved related issues, such as ungluing of the resilient material from the denture base, appearance of an unpleasant odor, change in the color or texture of the material, etc. In our study, dental practitioners and dental technicians use RDLMsfor complete denture lining mainly in clinical cases with presented pain symptoms.